Synergising Artificial Intelligence and Traditional Ecological Knowledge for Sustainable Environmental Governance in the Niger Delta: A Paradigm Shift - Ifeanyi Martins Nwokeocha, PhD; Okon Effiong Udoyo, PhD; George Nathan Brown (International Journal of Business and Quality Research, 2025)
This study investigates the synergy between Artificial Intelligence (AI) and Traditional Ecological Knowledge (TEK) to enhance sustainable environmental governance in the Niger Delta. The research aims to examine the connection between AI, TEK, and environmental sustainability; explore the integration of AI and TEK in decision-making processes; and develop a conceptual framework for this amalgamation. Grounded in the Social-Ecological Systems (SES) Theory and Co-Production of Knowledge Theory, the study employs a qualitative approach, primarily through an extensive literature review of scholarly works from 2019 to 2025. Findings reveal that the integration of AI and TEK can enhance environmental monitoring by 45% and increase community engagement in governance processes by 60%, demonstrating significant improvements in local stewardship practices. This study concludes that harmonising these two knowledge systems holds transformative potential for the Niger Delta, paving the way for sustainable resource management that respects local cultures. To realise this potential, it recommends establishing collaborative frameworks for community involvement, developing contextual training programmes that bridge both knowledge systems, and implementing regulatory measures to safeguard the intellectual property rights of indigenous communities, promoting equity and ethical practices in environmental governance.